Novel Insights Into the Mechanism of GVHD-Induced Tissue Damage - Ara, Takahide; Hashimoto, Daigo (Frontiers in Immunology, 2021)
Prophylaxis for and treatment of graft-versus-host disease (GVHD) are essential for successful allogeneic hematopoietic stem cell transplantation (allo-SCT) and mainly consist of immunosuppressants such as calcineurin inhibitors. However, profound immunosuppression can lead to tumor relapse and infectious complications, which emphasizes the necessity of developing novel management strategies for GVHD. Emerging evidence has revealed that tissue-specific mechanisms maintaining tissue homeostasis and promoting tissue tolerance to combat GVHD are damaged after allo-SCT, resulting in exacerbation and treatment refractoriness of GVHD. In the gastrointestinal tract, epithelial regeneration derived from intestinal stem cells (ISCs), a microenvironment that maintains healthy gut microbiota, and physical and chemical mucosal barrier functions against pathogens are damaged by conditioning regimens and/or GVHD. The administration of growth factors for cells that maintain intestinal homeostasis, such as interleukin-22 (IL-22) for ISCs, R-spondin 1 (R-Spo1) for ISCs and Paneth cells, and interleukin-25 (IL-25) for goblet cells, mitigates murine GVHD. In this review, we summarize recent advances in the understanding of GVHD-induced tissue damage and emerging strategies for the management of GVHD.